2013
DOI: 10.3109/10715762.2013.845294
|View full text |Cite
|
Sign up to set email alerts
|

Tempol-nebivolol therapy potentiates hypotensive effect increasing NO bioavailability and signaling pathway

Abstract: Nebivolol is a third generation beta blocker with endothelial nitric oxide synthase (eNOS) agonist properties. Considering the role of reactive oxygen species (ROS) in the uncoupling of eNOS, we hypothesized that the preadministration of an antioxidant as tempol, could improve the hypotensive response of nebivolol in normotensive animals increasing the nitric oxide (NO) bioavailability by a reduction of superoxide (O 2 .-) basal level production in the vascular tissue. Male Sprague Dawley rats were given tap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Therefore, we also tested VR-related metrics in both groups and found that the obs group showed significantly better improvements in these metrics. According to reports [ 16 , 17 ], Entresto has a dual-target regulation mechanism, and its mechanism of action is the same as that of enalapril. It can participate in natriuretic expansion, blood pressure reduction, myocardial remodeling reversal and cardiac function by inhibiting enkephalase and upregulating natriuretic peptide and bradykinin.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we also tested VR-related metrics in both groups and found that the obs group showed significantly better improvements in these metrics. According to reports [ 16 , 17 ], Entresto has a dual-target regulation mechanism, and its mechanism of action is the same as that of enalapril. It can participate in natriuretic expansion, blood pressure reduction, myocardial remodeling reversal and cardiac function by inhibiting enkephalase and upregulating natriuretic peptide and bradykinin.…”
Section: Discussionmentioning
confidence: 99%
“…•− and plasma malondialdehyde (MDA) levels, as well as a reduction in NO metabolites (NOx), have been described in L-NAME-induced hypertensive rats [5,6,17,18]. Subsequently, eNOS uncoupling has been demonstrated to be a major source of superoxide generations in L-NAME hypertensive rats [19,20]. Low levels of endogenous antioxidant enzymes, such as superoxide dismutase, catalase, and glutathione, have been noted in NO-deficient hypertensive rats [21].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we confirmed that nebivolol could upregulate the expression of iNOS in OSCC cells and contribute to the activation of the NO signal pathway. Nebivolol was reported to beneficiate the response of the NO signal pathway to relieve hypertension ( Varagic et al, 2010 ; Bertera et al, 2014 ). NO is synthesized by NO synthase (NOS) and as a multifunctional signaling molecule.…”
Section: Discussionmentioning
confidence: 99%